Title: Is Mild Idiopathic Polyhydramnios Associated with an Increased Risk for an Intrauterine Fetal Demise? A Retrospective Cohort Study - Pagan M; Strebeck R; Dajani N; Sandlin A; Ounpraseuth S; Manning N; Magann EF (Dove Medical Press, 2023)
Megan Pagan,1 Ryan Strebeck,1 Nafisa Dajani,1 Adam Sandlin,1 Songthip Ounpraseuth,2 Nirvana Manning,1 Everett F Magann1 1Department of Obstetrics and Gynecology, University of Arkansas for the Medical Sciences, Little Rock, AR, USA; 2Department of Biostatistics University of Arkansas for the Medical Sciences, Little Rock, AR, USACorrespondence: Everett F Magann, Department of Obstetrics and Gynecology, 4301 W. Markham St. Slot # 518, Little Rock, AR, 72205, USA, Tel +1 501-686-8345, Fax +1 501-526-7820, Email efmagann@uams.eduObjective: Antenatal fetal surveillance has been recommended for moderate/severe idiopathic polyhydramnios but not for mild idiopathic polyhydramnios. The purpose of this study is to determine if pregnancies with mild idiopathic polyhydramnios have an increased risk for an intrauterine fetal demise (IUFD).Methods: Medical records and amniotic fluid volume ultrasound data from 2016 to 2021 at a university medical center were examined. Pregnancies with fetal anomalies, fetal infection, isoimmunization, multiple gestation, maternal diabetes and oligohydramnios were excluded. Normal amniotic fluid volume was defined as an amniotic fluid index (AFI) < 24 cm which was compared to mild idiopathic polyhydramnios, AFI of ≥ 24.0 cm- 29.9 cm, and moderate/severe polyhydramnios which is an AFI ≥ 30 cm.Results: Of 12,725 patients meeting inclusion study criteria, there were 249 with idiopathic polyhydramnios (n = 249) which was associated with an increased odds of IUFD (aOR) of 3.27 (CI 1.50- 7.15), NICU admission (aOR 1.28, CI 0.96- 1.70), 5-minute APGAR score less than 7 (aOR 2.16, CI 1.52- 3.07), and large for gestational age infant (LGA) (aOR 4.04, CI 2.83- 5.78) compared to normal amniotic fluid volume (AFV). In the mild polyhydramnios group (n = 204, out of the 249 women with polyhydramnios) compared to the 12,476 pregnancies with normal AFV group, IUFD (aOR 3.38, CI 1.46- 7.82), NICU admission (aOR 1.19, CI 0.87- 1.64), 5-minute APGAR score less than 7 (aOR 1.68, CI 1.10- 2.55) and LGA (aOR 3.87, CI 2.59- 5.78). In moderate/severe polyhydramnios group (n = 45) compared to the normal AFV group, there was no increased odds of IUFD (aOR 2.78, CI 0.38- 20.29) or NICU admission (aOR 1.74, CI 0.93- 3.26) but an increased odds for a 5-minute APGAR score less than 7 (aOR 4.94, CI 2.57- 9.53) and LGA fetus (aOR 4.80, CI 2.26- 10.22).Conclusion: There is an increased odds of IUFD in pregnancies complicated by mild idiopathic polyhydramnios. Patients should be counseled on an increased odds of adverse pregnancy outcomes associated with idiopathic polyhydramnios, and in those pregnancies with mild idiopathic polyhydramnios, antenatal fetal surveillance should be considered.Keywords: amniotic fluid volume, mild idiopathic polyhydramnios, intrauterine fetal demise, IUFD, perinatal outcomes